2019
DOI: 10.33369/insight.14.1.36-50
|View full text |Cite
|
Sign up to set email alerts
|

ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN DI INDONESIA (Studi Kasus: Indek LQ45 Periode 2012-2016)

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh Ukuran perusahaan, Umur perusahaan, dan Rasio kas terhadap Profitabilitas (ROA) pada perusahaan yang terdaftar di Bursa Efek Indonesia tahun 2012-2016. Pengambilan sampel menggunakan metode purposive sampling dengan kriteria tertentu. Jumlah sampel yang digunakan dalam penelitian ini adalah 39 perusahaan yang tergabung dalam indeks LQ45 yang terdaftar di Bursa Efek Indonesia tahun 2012-2016. Penelitian ini menggunakan beberapa alat uji yaitu: uji asumsi klasik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
4
0
5
Order By: Relevance
“…Assets are the main problem in the occurrence of fraud. This study is in accordance with (Putra and Badjra, 2015), (Budiharjo, 2020), and (Juliana and Melisa, 2019), which show that company size has a negative and significant effect on the company's financial performance. Because the higher the size of the company, it has the ability to obtain capital, but the capital can be used by the company in increasing retained earnings for asset development, not to optimize company operations.…”
Section: The Influence Of Company Size On Company Financial Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…Assets are the main problem in the occurrence of fraud. This study is in accordance with (Putra and Badjra, 2015), (Budiharjo, 2020), and (Juliana and Melisa, 2019), which show that company size has a negative and significant effect on the company's financial performance. Because the higher the size of the company, it has the ability to obtain capital, but the capital can be used by the company in increasing retained earnings for asset development, not to optimize company operations.…”
Section: The Influence Of Company Size On Company Financial Performancesupporting
confidence: 90%
“…Companies that have a large size are not always free from legal cases in their operations, for that the company's operations are good for the convenience of the company in obtaining capital because in terms of the size of the company it must be carried out properly according to the mandate of the capital owner, even though sometimes companies actually use the capital by increasing company assets are not to optimize the company in order to increase the value of the company, as well as financial performance that has not been able to increase the value of the company. The previous research conducted by (Juliana and Melisa, 2019), (Muliana and Ikhsani, 2019), and (Widianingsih, Sadewo and Suparlinah, 2017), showed that profitability was not able to be an intervening variable from the influence of firm size on firm value. From these results, it is known that profitability, as proxied by ROE, does not have an indirect effect on the effect of firm size (SIZE) on firm value (PBV).…”
Section: The Effect Of Firm Size On Firm Value With Firm Financial Pe...mentioning
confidence: 91%
“…In this study, the profitability will be projected with the ROA (return on assets) ratio. According to Juliana & Melisa (2019), ROA is a ratio that functions to measure how the company's effectiveness is in generating profits by managing and utilizing its assets. The calculation using ROA will measure the net profit generated by the company, which is created from the contribution of assets owned by the company.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dapat disebabkan karena perusahaan besar membayar biaya operasional yang lebih besar dibandingkan perusahaan kecil sehingga dapat menurunkan laba perusahaan. Juliana & Melisa (2019) menjelaskan bahwa besarnya ukuran perusahaan tidak tentu didukung dengan pengelolaan sumber daya perusahaan yang efektif. Pomar et al, (2016) menegaskan perusahaan kecil dapat meningkat kinerja mereka dengan tindakan entrepreneurial orientation yaitu pemanfaatan kesempatan dalam menjalankan usaha mereka.…”
Section: Pembahasanunclassified